Exploring the hidden part of the iceberg: Post-partum weight retention among mothers and its association with sociodemographic, cultural and behavioural factors - Saranshi Nagpal; Smitha Chandrashekarappa; Sulochanadevi Chakrashali; J. Rakshitha; Narayana Murthy Mysore Ramaiah (Elsevier, 2021)
Introduction: India accounts for more than 2/3rd of total deaths due to NCD's and South East Asian Regions make up to 62% of disease burden. Obesity being major risk factor for NCD's, Post-Partum weight retention (PPWR) could be an important preventable predisposing factor, reducing one's risk of acquiring NCD's. Objectives: (1) Determine Post-Partum Weight Retention (PPWR) among Mothers at near one-year post delivery and determine its association with socio-demographic, cultural and behavioural factors. Methodology: It's a cross-sectional community based study, conducted at Urban -Primary Health Centres and Anganwadi centres of Mysuru, Karnataka, India among the mothers between 10 and 14 months post-delivery. Multi-stage sampling technique was adopted to recruit estimated sample size of 150 Mothers. Data on pre-pregnancy weight was obtained retrospectively from the Maternal and Child Health cards and present weight, waist circumference, hip circumference were measured using standardized procedures. Data on sociodemographic, cultural and behavioural factors were collected using culturally adopted pre-tested self-administered questionnaire. Data was analysed using SPSS V25 (Licensed to institution). Results: 91.3% Mothers retained weight post-partum. Among them, 55% had shifted to higher category of Body Mass Index. Significant Statistical difference was seen w.r.t waist circumference, hip circumference, frequency of breast feeding, consumption of cereals/fat, practice of food taboos and physical activity between mothers with PPWR and without PPWR. Conclusion and Recommendation: Significant Proportion of Mothers had PPWR. Routine maternal and child follow-ups post-delivery should be utilized for creating awareness on lifestyle changes to reduce PPWR.